Effect of Nb concentration on the spin-orbit coupling strength in Nb-doped SrTiO3 epitaxial thin films - Cho, Seong Won; Lee, Milim; Woo, Sungmin; Yim, Kanghoon; Han, Seungwu; Choi, Woo Seok; Lee, Suyoun (NATURE PUBLISHING GROUP, 2018)
Several oxide materials have attracted much interest for the application in spintronic devices due to unusual properties originating from the strongly correlated orbital and spin degrees of freedom. One missing part in oxide spintronics is a good spin channel featured by strong spin-orbit coupling (SOC) which enables an efficient control of the electron's spin. We have systematically investigated the dependence of the SOC strength of Sr(NbxTi1-x)O-3 thin films on Nb concentration (n(Nb) = 2 similar to 20 at. %) as a deeper exploration of a recent finding of the strong SOC in a heavily Nb-doped SrTiO3 (Sr(Nb0.2Ti0.8)O-3) epitaxial film. Apart from a finding of a proportionality of the SOC to n(Nb), we have observed an intriguing temperature dependence of the SOC strength and the anisotropic magnetoresistance (MR) in the intermediate n(Nb) region. These phenomena are associated with the temperature dependence of Lande g-factor and the change of the band structure, which is consistent with the result of density functional theory (DFT) calculation.
Keywords: LARGE LINEAR MAGNETORESISTANCE; LANDE G-FACTOR; TRANSPORT; TEMPERATURE; DEPENDENCE; PHYSICS